THE INFLUENCE OF WORK MOTIVATION, DISCIPLINE AND WORK CULTURE, ON PERFORMANCE THROUGH JOB SATISFACTION IN STATE MIDDLE SCHOOLS IN BATAM KOTA DISTRICT - Silvia Vitri; Indrayani; Muammar Khaddafi; Chablullah Wibisono; Ngaliman; Muhammad Gita Indrawan (RADJA PUBLIKA, 2023)
The research aims to examine the influence of work motivation, discipline and work culture on performance through job satisfaction at state junior high schools in Batam City District. The method used in this research is the descriptive and explanatory survey method, because it will describe each variable and explain the relationship between the variables studied. To implement operational research methods, a research design is needed that is adapted to the conditions of the depth of the research to be carried out. In this research, variable measurements were carried out using an interval scale. The interval scale is related to the Likert Scale, namely qualitative questionnaire questions made quantitative with answers. The data sources used in this research are primary data and secondary data. The results of the research show that motivation has a positive and significant effect on job satisfaction, discipline has a positive and significant effect on job satisfaction, culture has a positive and significant effect on job satisfaction, motivation has a positive and significant effect on performance, discipline has a positive and significant effect on performance, culture has a positive effect and significantly on performance, job satisfaction has a positive and significant effect on performance, job satisfaction significantly mediates the relationship between motivation and employee performance, job satisfaction significantly mediates the relationship between discipline and employee performance, and job satisfaction significantly mediates the relationship between motivation and employee performance.